An overview of herbs, spices, and plant extracts used as seasonings in food and meat processing (2013)
Man resorted to meat preservation as a means of keeping meat to be used at a later date. This he must do with appropriate, affordable and simple technologies to suit this need. This is particularly needful in developing nations as scarce food must not be allowed to waste, especially as the protein demand of the ever increasing population is rising. Salting and drying of meat dates back to antiquity, where the early man salted meat cuts on the exposed surfaces and hung them in the air to dry. Salt (a chief curing agent) in meat, and pepper form the basis of virtually all seasoning formulae. All other agents in seasoning (ingredients which improve the flavour of meat and foods) are supplementary to these as they form the integral part of various cuisines all over the world. Seasonings include Spices such as pepper, herbs such as the leaves of cloves and bay, vegetable bulbs such as garlic and onions, sweeteners such as sugar and monosodium glutamate, and plant extracts such as that of Ocimum grattisimum or ‘scent leaf. Spices are the bark, roots, seeds, buds or berries of plants, most of which grow naturally only in tropical climates.They are mostly used in their dried form, rarely fresh and are available whole or ground. Spices vary greatly in composition but the aromatic and pungent principles that render them valuable reside in their volatile oils, resins, or oleoresins. Herbs on the other hand refer to the larger group of aromatic plants whose leaves, stems or flowers are used to add flavour to foods. Herbs and spices in addition possess potential health benefits by inhibiting lipid peroxidation. Some of these seasonings include pepper, capsicum, turmeric, ginger, cloves, african nut meg, curry, the leaves of ocimum, cloves, thyme, onions and garlic. This paper seeks to give an overview of herbs and spices commonly used in tropical meat seasoning, their prospects and benefits to man’s health and well being.